2015
DOI: 10.1111/ans.13063
|View full text |Cite
|
Sign up to set email alerts
|

Training models for meniscal repairs and small joint arthroscopy

Abstract: Porcine stifles are cost effective, accessible, allow for meniscal repair and are suitable for arthroscopic access and view. Our view is that they are an ideal training model for arthroscopic meniscal repair, small joint arthroscopy and anterior cruciate ligament reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…It is especially challenging to achieve proficiency in arthroscopic surgery without hands-on repetition [13], and although computer simulators have been available for several years, fluid management, dynamic resistance, and haptic feedback are valuable simulation features afforded to the trainee learning on flesh-and-bone specimens. Training with human cadaveric models is expensive, and porcine knees, with anatomy similar to the human knee, are inexpensive and readily available [10,11,16,21]. Although arthroscopic training using porcine knees is not a novel concept, studies have not shown that the porcine knee is similar enough to the human cadaveric knee for arthroscopic skills assessment [3,10,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is especially challenging to achieve proficiency in arthroscopic surgery without hands-on repetition [13], and although computer simulators have been available for several years, fluid management, dynamic resistance, and haptic feedback are valuable simulation features afforded to the trainee learning on flesh-and-bone specimens. Training with human cadaveric models is expensive, and porcine knees, with anatomy similar to the human knee, are inexpensive and readily available [10,11,16,21]. Although arthroscopic training using porcine knees is not a novel concept, studies have not shown that the porcine knee is similar enough to the human cadaveric knee for arthroscopic skills assessment [3,10,21].…”
Section: Discussionmentioning
confidence: 99%
“…Training with human cadaveric models is expensive, and porcine knees, with anatomy similar to the human knee, are inexpensive and readily available [10,11,16,21]. Although arthroscopic training using porcine knees is not a novel concept, studies have not shown that the porcine knee is similar enough to the human cadaveric knee for arthroscopic skills assessment [3,10,21]. This study found that the porcine knee model demonstrated high face validity, because participants attained similar scores on both the human cadaveric and porcine specimens and high reliability with more experienced surgeons achieving higher scores using the porcine model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T he ideal training to improve the arthroscopic skills of trained surgeons and specialist surgeons is on human cadaver parts. 1 However, there are several difficulties in obtaining human anatomical pieces, such as their high cost (which can reach $500.00 for each piece), storage requirements, and ethical issues. [2][3][4] Alternatives to the use of human cadavers are training with artificial models, 3-dimensional simulators, and animal anatomical models, such as porcine and bovine knee.…”
mentioning
confidence: 99%
“…7 Several studies have already shown that some anatomical animal models are very close to humans and therefore apply well to the training of open and arthroscopic surgical skills. 1,9,10 The bovine model has already been used in several studies and shown itself to be an adequate animal model for arthroscopic training, mainly for arthroscopic triangulation training. 1,6,11 In this article, we describe, step by step, how to set up an arthroscopy laboratory with an anatomical animal model.…”
mentioning
confidence: 99%